The Integration of Restorative Justice Principles in the Handling of Narcotics Crimes Based on the Principles of Justice and Legal Reform - Sudiyanto, Sudiyanto; Israhadi, Evita Isretno (Ridwan Institute, 2025)
The rehabilitation of individuals struggling with addiction to narcotics, as outlined in Law No. 35/2009, underscores a two-pronged strategy that prioritises the recovery of health and social reintegration. This approach eschews criminal retribution in favour of more holistic methods of addressing the issue. The concept of restorative justice has emerged as an alternative approach to narcotics crime resolution, emphasising the recovery of offenders, victims and communities through dialogue and deliberation, rather than punishment. However, this approach is not without its challenges, and as such, the establishment of a robust legal framework is paramount. This research aims to integrate the concept and principles of restorative justice in the handling of narcotics abuse cases in Law No. 35/2009 based on the principle of justice and examine the legal reform of the application of restorative justice in the settlement of narcotics offences. The research method employed is a normative research method through a legislative approach and analytical approach. The results obtained demonstrated that the concepts and principles of restorative justice can be integrated in handling narcotics abuse cases based on Law No. 35/2009 to realise the principle of justice. The fundamental tenet of restorative justice emphasises the rehabilitation of individuals who use narcotics as a means of recovery, superseding the mere imposition of punishment. It is therefore imperative that a comprehensive revision of Law No. 35/2009 is made in order to incorporate the restorative justice approach on a more extensive scale.